3D stagnation point flow of Maxwell fluid towards an off-centered rotating disk. Issue 2 (8th August 2016) - Khan, Najeeb Alam; Khan, Sidra; Riaz, Fatima
Abstract : Purpose: This article is committed to study the three-dimensional, steady and incompressible flow of non-Newtonian rate type Maxwell fluid, for stagnation point flow towards an off centered rotating disk. Design/methodology/approach: The governing partial differential equations are transformed to a system of nonlinear ordinary differential equations by conventional similarity transformations. The non-perturbation technique, homotopy analysis method (HAM) is employed for the computation of solutions. And, the solution is computed by using the well known software Mathematica 10. Findings: The effects of rotational parameter and Deborah number on radial, azimuthal and induced velocity functions are investigated. The results are presented in graphical form. The convergence control parameter is also plotted for velocity profiles. The comparison with the previous results is also tabulated. The skin friction coefficients are also computed for different values of Deborah number. Originality/value: This paper studies the effect of rotation and Deborah number on off centered rotating disk has been observed and presented graphically.